2007
DOI: 10.1002/aqc.829
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Spanish white‐clawed crayfish (Austropotamobius pallipes) populations as determined by RAPD analysis: reasons for optimism

Abstract: ABSTRACT1. Spanish populations of the white-clawed crayfish have declined sharply over the last three decades. Although Austropotamobius pallipes was once widely distributed and very abundant in most of the limestone basins of the country, outbreaks of crayfish plague since 1978 have reduced its populations, and now only some 500-600 small populations are left.2. Consequently, the species now enjoys protection under national legislation. Management decisions regarding the conservation of a threatened species r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…Studies demonstrating low variation at mitochondrial markers suggested that populations in the Iberian Peninsula (belonging to A. italicus) had been introduced there by humans Trontelj et al, 2005). However, more detailed analyses revealed higher variation than previously assumed and suggested substantially longer presence of the species in this region (Beroiz et al, 2008;Diéguez-Uribeondo et al, 2008;Matallanas et al, 2011Matallanas et al, , 2013. Patterns suggesting bottlenecks, previously ascribed to human mediated introductions, are interpreted by survival in small-scale glacial refugia (Pedraza-Lara et al, 2010) and recent population crashes due to crayfish plague outbreaks and other negative factors (Matallanas et al, 2011(Matallanas et al, , 2013.…”
Section: > Austropotamobius Pallipes Species Complex; White-clawed Crmentioning
confidence: 77%
“…Studies demonstrating low variation at mitochondrial markers suggested that populations in the Iberian Peninsula (belonging to A. italicus) had been introduced there by humans Trontelj et al, 2005). However, more detailed analyses revealed higher variation than previously assumed and suggested substantially longer presence of the species in this region (Beroiz et al, 2008;Diéguez-Uribeondo et al, 2008;Matallanas et al, 2011Matallanas et al, , 2013. Patterns suggesting bottlenecks, previously ascribed to human mediated introductions, are interpreted by survival in small-scale glacial refugia (Pedraza-Lara et al, 2010) and recent population crashes due to crayfish plague outbreaks and other negative factors (Matallanas et al, 2011(Matallanas et al, , 2013.…”
Section: > Austropotamobius Pallipes Species Complex; White-clawed Crmentioning
confidence: 77%
“…Thereafter, the artificial spread of the species by humans would have resulted in its present-day distribution (Clavero and Villero 2013). Other authors, however, consider the white-clawed crayfish to be the only crayfish species native to the Iberian Peninsula (Alonso 2012;Beroiz et al 2008;Diéguez-Uribeondo et al 2008;Matallanas et al 2011Matallanas et al , 2012Pedraza-Lara et al 2010;Santucci et al 1997). The genetic arguments put forward against a native Spanish origin have mainly been the absence of genetic variation among and within populations and shared haplotypes between Italian and Spanish populations (Grandjean et al 2002a;Grandjean et al 2002b).…”
Section: Origin Of the Spanish White-clawed Crayfishmentioning
confidence: 94%
“…For the last few years, the genetic variability of Spanish white-clawed crayfish has been assessed with mitochondrial and nuclear markers by sampling a significant number of populations throughout its distribution range in the country (Beroiz et al, 2008;Matallanas et al, 2013Matallanas et al, , 2016PedrazaLara et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methods based on polymerase chain reaction (PCR) amplification have been successfully used to characterize genetic variability in the white-clawed crayfish (Amouret et al, 2015;Beroiz et al, 2008;Gouin et al, 2006; among many others). PCR-restriction fragment length polymorphism (PCR-RFLP), one of these methods, consists of the amplification of a DNA fragment, followed by restriction enzyme treatment and electrophoretic separation.…”
Section: Introductionmentioning
confidence: 99%